A back-linked Fabry–Pérot interferometer for space-borne gravitational wave observations. (21st May 2021) - Izumi, Kiwamu; Fujimoto, Masa-Katsu
Abstract: Direct observations of gravitational waves at frequencies below 10 Hz will play a crucial role in fully exploiting the potential of gravitational wave astronomy. One approach to pursue this direction is the utilization of laser interferometers equipped with Fabry–Pérot optical cavities in space. However, there are a number of practical challenges in following this path. In particular, the implementation of precision control for cavity lengths and the suppression of laser phase noises may prevent a practical detector design. To circumvent such difficulties, we propose a new interferometer topology, called a back-linked Fabry–Pérot interferometer, where precision length controls are not required and an offline subtraction scheme for laser phase noises is readily applicable. This article presents the principle idea and the associated sensitivity analyses. Despite additional noises, a strain sensitivity of 7×10^-23 Hz^-1/2 may be attainable in the decihertz band. Several technological developments must occur and studies must be carried out to pave the way for the implementation.